Ergonomic Participatory in Halal Assurance System (HAS) Implementation to Reduce Boredom and Fatigue in Workers in the Sate Bandeng Processing Industry - Wahyu Susihono (Journal of Global Pharma Technology, 2019)
Every processing industry that has obtained a halal certificate from LPPOM MUI is obliged to maintain and maintain the implementation of Halal Assurance System (HAS), as well as sixteen halal certified milkfish satay processing industries from LPPOM-MUI Banten Province. However, in general the implementation of HAS-23000 has been carried out, but there are still weaknesses that need to be fixed. This weakness lies in the awareness of meeting the criteria and data updates by the company's internal halal management team. This weakness is due to the fulfillment of HAS that does not concern the human factors that carry out activities in the company. Humans are still considered as a complementary part of the company's business processes, not used as part of the main factors in the implementation of HAS-23000. Ergonomic Participatory Intervention needs to be done to improve employee performance seen from a decrease in work boredom and work fatigue. The subjects in this study were workers in 16 processing industries that were randomly selected; the sample fulfilled the inclusion criteria of the study. The design of this study was experimental research (treatment by subject design). Subjects in 16 processing industries, prior to the ergonomic participatory intervention, the initial observation (group I) was conducted, then the subject became an intervention group (application of ergonomic partitioning) referred to as group II. Result: The results showed that after an intervention in the form of ergonomic participatory implementation in the implementation of Halal Assurance System (HAS) in 16 milkfish satay processing industries, the mean of work boredom in group I was 89.44 ± 4.53 and group II was 65.69 ± 4.69 or decreased 26 , 64%, the average general fatigue in group I was 93.69 ± 10.85 and group II 83.13 ± 12.28 or a change of 11.27%, general fatigue felt by workers in 16 industries there were significant differences after an ergonomic participatory intervention (p <0.05 ), while fatigue in the aspect of activity experienced a change of 5.30%, fatigue in the aspect of motivation experienced a change of 24.38%, fatigue in the physical aspect experienced a change of 12.58%. Fatigue in the aspects of motivation and physical aspects there is a very significant change, but in the fatigue aspect of the activity changes that occur is not significant p> 0.05). Intervention with ergonomic participatory can improve employee performance in halal certified satay milkfish food processing industry, seen from the decrease in the level of boredom and work fatigue (general fatigue, activity fatigue, motivation fatigue and physical aspect fatigue). Decreased boredom also occurs (26.64%), indicating that there has been an increase in employee performance as indicated by an improvement in employee mental perceptions. Improved employee performance shows an improvement in the implementation of the criteria in the Halal Assurance System (HAS).Keywords: HAS-23000, Halal, Participatory ergonomics, Boredom, Fatigue.